Labour law of Serbia in the XX and XI century - Jašarević Senad R. (Zbornik Radova: Pravni Fakultet u Novom Sadu, 2018)
At the turn of the two millennia, it seemed that the labour laws of the XX and XXI centuries would not be much different. Under the influence of globalization, the economic crisis, information technology, the circumstances in which the work is taking place in the meantime have changed significantly, and workers, employers, labor relations and labour law have also been changed. The paper presents the current changes in the field of labor relations, the changes of the working legislation that are expected in the future in the world and in Serbia.